Impulsy ze strony teologicznej myśli Karla Rahnera SJ (1904-1984) i teologii narracyjnej w kierunku pogłębienia teologii imienia Jezus - Bokwa, Ignacy (Poznańskie Studia Teologiczne, 2018)
The theological dimension of the name of Jesus is not only a domain of biblical teaching, pa- trology, theology of spirituality or theology of liturgy. It is also a eld for re ection of systematic theology. This study starts with a brief theological analysis of the name of Jesus and states that this is a summary of His earthy mission which is a saving mission to man and the world. Karl Rah- ner’s contribution to contemporary christological re ection is hard to overestimate. His so-called transcendental christology is an attempt to include anthropology into the structure of theology as its integral component. In contrast, narrative theology deals with modern man as the addressee of the Christian message about salvation. It develops particular ways of access by a man, who is not a believer, to the Person and work of Jesus of Nazareth as the true and living Son of God.